(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article analyzes the role of private entrepreneurship and small business entities in socioeconomic development of the region, using the Khorezm region as a case study, and examines the issues of their stimulation through tax incentives. Throughout the research, the position of small business entities within the regional economy is analyzed, and the role of small business in ensuring public employment is studied. The significance of the taxation system in enhancing the investment opportunities of small business entities is evaluated. Furthermore, the study is conducted based on statistical reports across 12 districts of this region, exploring the efficiency of small businesses and the matters of their stimulation through taxation.